Treating wastewater in a conventional activated sludge (CAS) system or a Membrane Bioreactor (MBR). A comparison of capital and operating costs - Smith, Delwin (Department of Civil Engineering, 2020)
More and more focus is going into the establishment of more sustainable approaches for wastewater treatment (WWT) in South Africa, as well as around the world. Governments are beginning to enforce more economical solutions for WWT, which will have less impact on costs as well as land area requirements. Effective solid-liquid separation in biological wastewater treatment is an important step in the process as it has a major impact on effluent quality. Traditionally this has been achieved using Secondary settling tanks (SSTs) for liquid/solid separation in combination with a biological reactor (for biological degradation of organic matter). SSTs, however, require a large space, which becomes onerous on land requirements. In an immersed membrane bioreactor (iMBR), solid-liquid separation takes place by the wastewater passing through membranes. As the WW flows through, at the same time solids are rejected by the membranes. These membranes are immersed in the bioreactor. iMBR thus eliminates the requirement for SSTs and are becoming more widely used to treat various types of wastewater, due to the decreasing cost of membranes and the resultant reduced plant footprint. MBR is thus becoming an attractive solution to clients due to its sustainable approach. As part of this investigation, 2 types of MBR technology were included, the Kubota FS MBR system and the Zeeweed HF MBR system. As the design of a CAS is sensitive to sludge settleability, various DSVI values were looked at as part of the CAS system. Each system was configured in an MLE and UCT process. In summary, the following systems were included in this investigation: • CAS in an MLE configuration with DSVI of 100,150 and 200 • CAS in a UCT configuration with DSVI of 100,150 and 200 • iMBR using FS membranes in an MLE configuration • iMBR using FS membranes in a UCT configuration • iMBR using HF membranes in an MLE configuration • iMBR using HF membranes in a UCT configuration Each process configuration was designed and sized using the steady state models. Each configuration was then fully costed using actual construction prices from past and current projects. Costing of the MBR systems were done in conjunction with the membrane suppliers who also provided valuable design input. The selection of design MLSS in an MBR and CAS has a significant impact on the reactor and SST size. The MLSS concentration also has an impact on the alpha factor which influences aeration efficiency. As part of this investigation, an optimum MLSS concentration (MLSSopt) cost optimization was done taking into account the effect on reactor size, SST area, membrane area, and aeration CAPEX and OPEX. This resulted in an MLSSopt of 5 500 mg/l and 6 000 mg/l for the CAS MLE and CAS UCT respectively, and 10 000 mg/l for the Zeeweed MBR and Kubota MBR system. The CAS system had the lowest total cost (CAPEX+OPEX) of the 3 systems over a lifespan of 10 years, with the Zeeweed MBR having the 2 nd lowest cost coming in at 61% higher than the CAS system. The Kubota MBR had the highest total cost with a 203% higher cost than the CAS system. In terms of land area requirement, the Kubota MBR required the least amount of land area, followed by the Zeeweed MBR which required 12% more land space. The CAS system required 127-514% more land space at the various DSVI values than the Kubota system. This was due to the additional SST area and a larger reactor requirement.